Caregivers, Caseworkers, and Biological Parents: Risk Factors for Foster Teen Pregnancy and Ways You Can Make a Difference - Nora Del Giudice; Stephanie Toelle; David C. Diehl; Jody S. Nicholson (EDIS)
Many teens exhibit risk-taking behavior. That said, the past experiences of foster care youth in particular make them likely to engage in activity that could cause teen pregnancy and sexually transmitted infections. This 9-page fact sheet is designed to provide kin and foster caregivers, caseworkers, and biological parents of children in foster care with information about the physical, emotional, and psychological concerns related to teen reproductive health in the foster care system. It also aims to help all involved identify the risk factors associated with foster teen pregnancy and explains legal rights regarding foster teen health. Written by Nora Del Giudice, Stephanie C. Toelle, David C. Diehl, and Jody S. Nicholson, and published by the UF Department of Family, Youth and Community Sciences, May 2016.